Hepatic steatosis alters cellular recruitment during induced aerocystitis in Nile tilapia - Moraes, Alessandra C. [UNESP]; Prado, Ed J.R. [UNESP]; Foz, Elizabeth P.; Barbuio, Roberto [UNESP]; Faria, Vanessa P.; Belo, Marco A.A. [UNESP] (FapUNIFESP (SciELO), 2018)
The study evaluated the hepatotoxicity induced by CCl4 during the glucocorticoid effect of dexamethasone (DEX) on the pathophysiology of the acute inflammatory reaction in Nile tilapia, Oreochromis niloticus, correlating hepatic functionality with cellular accumulation kinetics in infectious aerocystitis. Eighty- four Nile tilapia were distributed into four treatments: control, CCl4, DEX and CCl4 + DEX. Seven tilapia were sampled per treatment in three periods: 6, 24 and 48h after induction of inflammation. CCl4 was used in a single dose of 0.5mL/kg intraperitoneally to cause hepatic disorder. Aeromonas hydrophila inoculum was used to induce aerocystitis. Dexamethasone was administered intramuscularly at the dose of 2mg/kg b. w. The results revealed a higher serum aspartate transaminase (AST) activity associated with greater somatic liver alteration, being these findings inversely proportional to the cellular accumulation in the inflammatory focus, demonstrating a lower number of inflammatory cells in the animals affected with a higher degree of hepatic disorders induced by CCl4. The histopathological study revealed transient degenerative changes in the most acute phase, as livers of tilapia showed accumulation of lipids in hepatocytes 6 hours after administration of CCl4, and this fatty degeneration was no longer observed in 24 and 48h. However, administration of CCl4 in Nile tilapia resulted in acute and transient liver degeneration, characterized by accumulation of fat in hepatocytes, increased AST in the blood and hepatomegaly. With liver dysfunction there was compromise of cellular recruitment in infectious aerocystitis, indicating that there is liver involvement in the innate immune response in tilapia.
Esteatose hepática altera acúmulo celular em tilápias do Nilo durante aerocistite infecciosa
Keywords: Acute inflammation; Aerocystitis; Carbon tetrachloride; Cichlid fish; Glucocorticoid; Hepatic steatosis; Tilapia